Development and Full Validation of a Monte Carlo Single-photon Emission Computed Tomography Camera Proposed for Coded Aperture Breast Tumor Imaging - Hussain, Khalid (Asian Journal of Pharmaceutics (AJP), 2025)
The Modified Uniformly Redundant Array (MURA) Coded Aperture (CA) imaging technique, initially developed for astronomical X-rays in far-field geometry, offers high Signal-to-Noise Ratio (SNR) and artifact-free imaging. Interest has grown in adapting MURA-CA to near-field geometry due to its high sensitivity and superior resolution, despite challenges related to artifacts. Materials & Methods: This study utilized MURA masks, anti-masks, and subtraction techniques to exploit their delta correlation function. Simulations were conducted with varying planar source sizes using 140 keV photons and Gaussian blurring to replicate real-world conditions. Separate decoding functions were applied to reconstruct images from mask- and anti-mask-projected data. Metrics including resolution Full Width at Half Maximum (FWHM), contrast, SNR, root-mean-square error (RMSE), and correlation coefficients were evaluated. Results: MURA-CA exhibited significant SNR advantages compared to pinholes and collimators. Near-field imaging, however, introduced artifacts that could be mitigated by transitioning to far-field geometry, though at the expense of counting efficiency and SNR. Subtraction of mask and anti-mask images effectively minimized side lobe effects and reduced RMSE, achieving results comparable to individual mask and anti-mask projections. Further enhancements were made by optimizing the trade-off between SNR and resolution under fixed time and dose conditions. Conclusion: MURA-CA is particularly well-suited for far-field applications like breast tumor imaging, where artifacts are minimal. This study highlights the potential of a MURA-CA system specifically designed for high-resolution SPECT imaging, integrated with a clinical gamma camera, to enable early tumor detection with improved imaging performance.